2020
DOI: 10.1177/0954407020916940
|View full text |Cite
|
Sign up to set email alerts
|

Dual-mass flywheels with tuned vibration absorbers for application in heavy-duty truck powertrains

Abstract: As the heavy-duty combustion engine development goes towards lower rotational speeds and higher cylinder pressures, the torsional vibrations increase. There is therefore a need to identify and study new types of vibration absorbers that can reduce the level of torsional vibrations transmitted from the engine to the gearbox. In this work, the concept of a dual-mass flywheel combined with a tuned vibration absorber is analysed. The tuned vibration absorber efficiently reduces the vibration amplitudes for engine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The torsional vibration of the powertrain system significantly influences the fatigue life of rotary components and the noise, vibration, and harshness (NVH) performance of the vehicle. [1][2][3][4] Even though the torsional damper is integrated in the clutch, 5 the torsional vibration problems of the powertrain system, such as the driveline shuffle, [6][7][8] clutch judder, [9][10][11][12] gear rattle, 13,14 and powertrain torsional resonance, 15,16 are still encountered under the excitation of the fluctuating torque of the engine. Among the vibration problems above, the powertrain torsional resonance is one of the most harmful, because it not only induces the abnormal 1 vibration and booming noise in the cabin, but also accelerates the fatigue damage of driveline components.…”
Section: Introductionmentioning
confidence: 99%
“…The torsional vibration of the powertrain system significantly influences the fatigue life of rotary components and the noise, vibration, and harshness (NVH) performance of the vehicle. [1][2][3][4] Even though the torsional damper is integrated in the clutch, 5 the torsional vibration problems of the powertrain system, such as the driveline shuffle, [6][7][8] clutch judder, [9][10][11][12] gear rattle, 13,14 and powertrain torsional resonance, 15,16 are still encountered under the excitation of the fluctuating torque of the engine. Among the vibration problems above, the powertrain torsional resonance is one of the most harmful, because it not only induces the abnormal 1 vibration and booming noise in the cabin, but also accelerates the fatigue damage of driveline components.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic vibration absorbers are generally a simple and cost effective vibration reduction measure and consist in their simplest form of a mass and spring with natural frequency adjusted to result in a counter force at a desired frequency to reduce the vibrations of the primary vibration system they are attached to. Their application area is found in a wide range since their first patent by Frahm [ 1 ], including earthquake protection of engineering constructions, reduction of human walk induced vibrations of engineering constructions, reduction of wind induced power transmission line vibrations, reduction of driveline vibrations in vehicles and reduction of aircraft and spacecraft vibrations [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Over the years, the design of dynamic vibration absorbers has evolved in various directions, including multiple, nonlinear, composite, continuous, active and semi-active dynamic vibration absorbers, see, e.g., Refs.…”
Section: Introductionmentioning
confidence: 99%
“…However, increasing demand for a higher efficiency of truck powertrains requires novel solutions. The research is ongoing both in academia as well as in industry to understand if a DMF as well as other multiple-mass absorbers are suitable for application in powertrains of heavy-duty trucks [18][19][20][21][22][23][24]. The idea of tuned Machines 2020, 8, 50 2 of 13 mass damper, successfully used in a variety of engineering applications [25][26][27][28][29], was also applied to modify a DMF performance.…”
Section: Introductionmentioning
confidence: 99%
“…The idea of tuned Machines 2020, 8, 50 2 of 13 mass damper, successfully used in a variety of engineering applications [25][26][27][28][29], was also applied to modify a DMF performance. In recent work [19,21,22], DMFs with and without a tuned mass damper were studied for application to the powertrain of a heavy-duty truck. It was concluded that an optimally design tuned mass damper could reduce the amplitude of oscillations of the torque at the transmission input shaft more than corresponding conventional DMF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation